If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2f + 3 = 11f + -24 Reorder the terms: 3 + 2f = 11f + -24 Reorder the terms: 3 + 2f = -24 + 11f Solving 3 + 2f = -24 + 11f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-11f' to each side of the equation. 3 + 2f + -11f = -24 + 11f + -11f Combine like terms: 2f + -11f = -9f 3 + -9f = -24 + 11f + -11f Combine like terms: 11f + -11f = 0 3 + -9f = -24 + 0 3 + -9f = -24 Add '-3' to each side of the equation. 3 + -3 + -9f = -24 + -3 Combine like terms: 3 + -3 = 0 0 + -9f = -24 + -3 -9f = -24 + -3 Combine like terms: -24 + -3 = -27 -9f = -27 Divide each side by '-9'. f = 3 Simplifying f = 3
| 3p=-4 | | -2x-4-6y+15=-11 | | -2x-4-6y+15=11 | | -b/2(a) | | 9c=4 | | 6x/3x | | -2+7x=45 | | 4d+(-11)=2d+7 | | 2x-11+4x-22=180 | | X+51=-62 | | 15=4x-55 | | 2m+9=7m-36 | | 9x^2+4x-3=7x^2-2 | | C=5/2k-47 | | y=0.036x^2-2.8x+62.57 | | 4(4w+3)*3=-11 | | C=5/2k-37 | | (-7x+13)(-x-8)=0 | | 5(2x+3)-6(-2x+1)=9(x-2) | | 2[x-2(x-1)]-3(3y-5)=-11 | | (2x-5)2-(x+1)2=7x | | -5(2t+2)=20 | | n+(-12)=3n | | X-2x+3=4x+2 | | 9x-9=9-8x | | 8x-16-2x=34 | | 12ab-28bc+20ac=0 | | x^(2/#)=1/3 | | 10x=0.000001 | | 3t^2-16t+21=0 | | -2x-6y+11=-11 | | 4n+21=-3 |